1989
DOI: 10.1128/aem.55.11.2789-2792.1989
|View full text |Cite
|
Sign up to set email alerts
|

Most-probable-number procedures for enumerating ruminal bacteria, including the simultaneous estimation of total and cellulolytic numbers in one medium

Abstract: Based on results from eight experiments, no overall difference was found between roll tube and three-and five-tube most-probable-number (MPN) methods for estimating total numbers of ruminal bacteria. However, standard errors for the replicate means within an experiment were higher with the MPN procedures. Visual growth and pH were the criteria used for scoring the MPN tubes. Total numbers were significantly higher in MPN medium containing 40% ruminal fluid, as compared with a complete medium without ruminal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 15 publications
1
26
0
2
Order By: Relevance
“…However, we found that this method also grew bacteria which were not cellulolytic and subsequent experiments (Mackie and McSweeney, unpublished data) have shown that many strains of cellulolytic bacteria growing in broth culture will not grow on or within this type of selective agar medium. In our laboratory, the MPN procedure (Dehority et al 1989) based on cellulose degradation in broth culture was a more reliable method for the enumeration of cellulolytic bacteria and acidswollen cellulosic ®lter paper supported the growth of a larger population of cellulolytic bacteria than cotton thread. Cotton thread tends to select for Fibrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we found that this method also grew bacteria which were not cellulolytic and subsequent experiments (Mackie and McSweeney, unpublished data) have shown that many strains of cellulolytic bacteria growing in broth culture will not grow on or within this type of selective agar medium. In our laboratory, the MPN procedure (Dehority et al 1989) based on cellulose degradation in broth culture was a more reliable method for the enumeration of cellulolytic bacteria and acidswollen cellulosic ®lter paper supported the growth of a larger population of cellulolytic bacteria than cotton thread. Cotton thread tends to select for Fibrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic colonies were counted as those with clearing zones after the casein agar plates were¯ooded with 1 mol l )1 HCl. Cellulolytic bacteria were also enumerated in broth medium using the MPN procedure described by Dehority et al (1989). The cellulose broth medium was the same as that used in the cellulose agar medium except that trypticase and yeast extract were omitted and the ball-milled cellulose (Sigmacell-20; Sigma Chemical, St. Louis, MO, USA) was replaced with either four pieces of cotton thread (1 mm diameter and 50 mm long; GIMP soft cotton; Coats, Brisbane, Australia) or four discs (5 mm diameter) of acid-swollen ®lter paper (Whatman no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunological techniques have been used to study cellulase activity in bacteria (Huang et al 1990). Refined culture procedures (Dehority et al 1989) have been developed for the enumeration and detection of cellulolytic bacteria in the rumen system.…”
Section: Introductionmentioning
confidence: 99%
“…The total caecal bacterial population size was estimated by the most probable number procedure, culturing serial dilutions of 1 g caecal content from each rabbit in complete medium (Dehority et al, 1989) for 7 days. All tubes were cultivated anaerobically in triplicate and growth was defined as having taken place in those tubes where the pH value was 0.2 U or less than the maximum dilution value.…”
Section: Enumeration Of Total Viable Anaerobic Bacteria and Vfa Analysismentioning
confidence: 99%